Research on the Impact of Financial Derivatives on Companies in the Energy Industry - Chen Shengyuan (SHS Web of Conferences)
In recent years, the development of the new energy industry has attracted more and more attention from countries focusing on coping with the energy crisis and economic upward development so that financial derivatives as a financial instrument need to be further explored for their value to companies. This paper selects a case study on the risk resilience, market competitiveness, financial management level and business expansion of China’s leading energy company Baolihua New Energy before and after the systematic intervention of financial derivatives, aiming to explore how the intervention of financial derivatives affects the development of new energy enterprises in many aspects. Through a single-case study approach, the findings show that with the help of derivatives such as futures, both the purchase of raw materials and the packaging and sale of outputs are more efficient and more certain. The intervention of financial derivatives can help energy companies reduce price risk and play an important role in capital chain, market share and territorial expansion further. Meanwhile, this paper points out that derivatives could put forward an effective way for new energy enterprises to develop positively in financial derivatives in order to adapt to the development of the times.